People with dementia in long-term care facilities: an exploratory study of their activities and participation - Rocha, Vânia (2013)
Purpose: To describe the activities and participation of people with dementia living in long-term care facilities. Methods: An exploratory descriptive study with 329 people medically diagnosed with dementia was conducted in the central region of Portugal. Socio-demographics were collected with a questionnaire based on the International Classification of Functioning, Disability and Health-Checklist. Cognitive impairment was measured with the Mini-Mental State Examination (MMSE) and the activities and participation were described with the World Health Organisation Disability Assessment Schedule 2.0 (WHODAS 2.0). Results: Participants mean age was 83.6 ± 7.1 years old. Most were female (79.6%), widows (60.8%), had 1–4 years of education (51.1%) and were living in a long-term care facility from 2 to 4 years (36.2%). Alzheimer’s disease (41.9%) was the most prevalent type of dementia. According to the MMSE, the cognitive status was low (8.7 ± 7.9) and 61.7% had severe cognitive impairment. The MMSE scores were negatively correlated with the WHODAS 2.0 scores. Mobility was the most affected domain of WHODAS 2.0. The total score showed that 77.8% of the sample was severely limited in activities and restricted in participation. Conclusions: This study shows that people with dementia living in long-term care facilities have severe activities limitation and participation restriction. However, most residents understand what people say, eat by themselves and get along with people who are close to them. This information on disability is crucial to plan health resources and inform rehabilitation programmes tailored to individuals’ functionality. Implications for Rehabilitation People with dementia living in long-term care facilities have severe activities limitation and participation restriction. Rehabilitation through engagement in activities and enhancement of participation seems to be crucial for this population. A multidimensional characterisation of activities and participation is recommended to inform the design and implementation of rehabilitation. Mobility was the most affected domain, highlighting the need for specific rehabilitation, as mobility restrictions are associated with residents’ dependency and caregivers’ burden.